From poverty to power: how active citizens and effective states can change the world - and Green, Duncan (Oxfam GB, 2012)
From Poverty to Power From Poverty to Power argues that a radical redistribution of power, opportunities, and assets rather than traditional models of charitable or government aid is required to break the cycle of poverty and inequality. The forces driving this transformation are active citizens and effective states. Published in association with Oxfam GB. Full description